miştir. Design of A Two Axis Line of Sight Stabilization System for Vessels - Necmi ALTIN; Melih SARP (Gazi Üniversitesi Fen Bilimleri Dergisi, 2017)
By preventing the angular vibrations of the platform from being carried on to the axes of the attached imaging or laser systems, line of sight stabilization allows both a stable image to be obtained and a stable marker to be created. In this study, a two axis gimbal system that can be used in vessels and can be subjected to low frequency disturbances is designed. Instead of using direct drive DC torque motors which are usually used as an actuator in these kinds of systems, a brushless DC motor with an output connected to a harmonic drive gear was considered. Because a harmonic drive gear is enough to provide the required stabilization precision, there is no need for large and heavy direct drive motors which are necessary under high frequency disturbances. In this paper, firstly an angular velocity and torque relationship derived. The cross-coupling effect resulting from torque disturbances, which are themselves created due to the effects of the motions on the elevation and azimuth axes on other axes, was then calculated. Finally, a stabilization loop was designed for every axis using the vector control method and the brushless DC motor’s mathematical model. The entire model was then simulated in the Simulink and results were discussed.